2021
DOI: 10.1186/s12913-021-06583-1
|View full text |Cite
|
Sign up to set email alerts
|

Advancing discussion of ethics in mixed methods health services research

Abstract: Background To describe the ethical issues and experiences of scientists conducting mixed methods health services research and to advance empirical and conceptual discussion on ethical integrity in mixed methods health research. Methods The study was conducted with 64 scholars, faculty and consultants from the NIH-funded Mixed Methods Research Training Program (MMRTP) for the Health Sciences. This was a cross-sectional study. Survey results were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Worryingly, studies have found that many mixed methods investigators do not consider their ethics training useful for planning, conducting, and reporting their research (Stadnick et al, 2021). These findings raise the important issue of how to prepare mixed methods researchers to recognize, seize, and address ethical dilemmas.…”
Section: Ethics In Mixed Methods Researchmentioning
confidence: 99%

Pragmatism and Methodology

Gillespie,
Glăveanu,
de Saint Laurent
2024
“…Worryingly, studies have found that many mixed methods investigators do not consider their ethics training useful for planning, conducting, and reporting their research (Stadnick et al, 2021). These findings raise the important issue of how to prepare mixed methods researchers to recognize, seize, and address ethical dilemmas.…”
Section: Ethics In Mixed Methods Researchmentioning
confidence: 99%

Pragmatism and Methodology

Gillespie,
Glăveanu,
de Saint Laurent
2024
“…In MMR, the ethical dilemmas that posed the greatest challenges revolved around addressing participant burden, communication, and dissemination. 10 Hence, emphasis to be placed on the necessity to ensure the well-being of participants, uphold privacy and confidentiality, and approach sensitive subjects with empathy and respect.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…First, we provide conceptual arguments for their inclusion. Second, drawing from seminal literature (Cain et al, 2019;Creswell & Plano Clark, 2007;Hall, 2013;Hesse-Biber, 2010;Poth, 2018;Shannon-Baker, 2016;Stadnick et al, 2021;Teddlie & Tashakkori, 2009), we developed criteria for the additional elements. As with the original elements, we independently reviewed all 66 documents and met to compare responses and resolve discrepancies.…”
Section: Development Process For the Expanded Frameworkmentioning
confidence: 99%
“…Research ethics has been a major consideration since the late 1970s when the Belmont Report was issued. This also applies to mixed methods research (Hesse-Biber, 2010;Poth, 2018;Stadnick et al, 2021). Since ethical considerations should inform the steps taken by researchers and are important for reporting quality (Fàbregues & Molina-Azorín, 2017;Howell Smith & Shanahan Bazis, 2021), a demonstration of ethical inquiry is needed in high-rigor methodological practice (Cain et al, 2019).…”
Section: Additional Advanced Elements: Paradigm and Ethicsmentioning
confidence: 99%